Balfour’s Legacy: Britain, Zionism, and the Controversial Path to Israel’s Establishment - Qader, Ali Mohammed (Arab Journal for Sciences and Research Publishing, 2024)
The research provides an overview of the rise of the Zionist movement, starting from the establishment of the Jewish Colonial Society in 1891 by Maurice de Hirsch, leading to the formation of the World Zionist Organization and the creation of the Jewish National Fund in 1901. It discusses the controversial debates over the location of a Jewish homeland, including the Uganda Scheme, and the advocacy for Palestine by figures like Herzl. The impact of World War I on the Middle East was influenced by the Sykes-Picot Agreement of 1916 and the Balfour Declaration of 1917, which supported the establishment of a Jewish national home in Palestine. The British Mandate in Palestine, established after the collapse of the Ottoman Empire, had significant impacts on Jewish immigration, Arab displacement, and the road to statehood. The United Nations eventually issued a resolution in 1947 to divide Palestine into two states, one for Jews and one for Arabs. This was accepted by Jews but rejected by Arab states. Great Britain’s actions towards the end of the mandate aimed to frustrate the establishment of the Jewish state envisioned by the United Nations plan. Drawing on primary and secondary sources from esteemed archives such as the British Library and personal accounts, this research seeks to elucidate the complex historical backdrop, contextualizing key decisions and conflicts that ultimately shaped the creation of the State of Israel. The analysis aims to provide nuanced insights into divergent perspectives held by Palestinians and Israelis regarding the resolution of this enduring conflict, rooted in a legacy of geopolitical manoeuvring and ideological fervour.